Data linkage can reduce the burden and increase the opportunities in the implementation of Value-Based Health Care policy: a study in patients with ulcerative colitis (PROUD-UC Study) - Walshe, John David; Akbari, Ashley; Hawthorne, A Barney; Laing, Hamish (International Journal of Population Data Science, 2022)
Introduction Healthcare systems face rising demand and unsustainable cost pressures. In response, health policymakers are adopting Value-Based Health Care (VBHC), targeting available resources to achieve the best possible patient outcomes at the lowest possible cost and actively disinvesting in care of low-value. This requires the evaluation of longitudinal clinical and patient reported outcome measures (PROMs) at an individual-level and population-scale, which can create significant data challenges. Achieving this through routinely collected electronic health record (EHR) data-linkage could facilitate the implementation of VBHC without an unacceptable data burden on patients or health systems and release time for higher-value activities. Objectives Our study tested the ability to report an international, patient-centred outcome dataset (ICHOM-IBD) using only anonymised individual-level population-scale linked electronic health record (EHR) data sources, including clinical and patient-reported outcomes, in a cohort of patients with moderate-to-severe ulcerative colitis (UC), receiving biopharmaceutical therapies ("biologics") in a single, publicly funded, healthcare system. Results We identified a cohort of 17,632 patients with UC in Wales and a cohort from two Health Boards of 447 patients with UC receiving biologics. 112 of these patients had completed 866 condition-specific PROMs during their biologics treatment. 44 out of 59 (74.6%) items in the ICHOM-IBD could be derived from routinely collected data of which a primary care source was essential for eight items and desirable for 21. Conclusions We demonstrated that it is possible to report most but not all the ICHOM-IBD outcomes using routinely collected data from multiple sources without additional system burden, potentially supporting Value-Based Health Care implementation with population data science. As digital collection of PROMs and use of condition-specific registries grow, greater utility of this approach can be anticipated. We have identified that the availability of longitudinal primary and secondary care data linked with PROMs is essential for this to be possible.